Influence of Cobalt Substitution in LaMnO3 on Catalytic Propylene Oxidation - Teotone Inas Mariano Vaz; Sridhar Maruti Gurav; Arun Vithal Salker (Universitas Gadjah Mada, 2021)
Perovskite-type structures LaBO3 with the compositions of LaMn1-xCoxO3 (x = 0.0, 0.3, 0.5, 0.7, and 1.0) were synthesized at 800 °C by a modified co-precipitation precursor technique for total oxidation of propylene, as a model test of the hydrocarbon oxidation reaction. Details concerning the evolution of the crystal structure, morphology, and crystallite size were performed by X-ray diffraction (XRD), Thermo Gravimetry Analysis (TGA)/Differential Scanning Calorimetry (DSC), Fourier Transform Infra-Red (FTIR), Atomic Absorption Spectroscopy (AAS), Scanning Electron Microscopy (SEM), and Electron Spin Resonance (ESR) techniques. All compositions were identified to be single-phase and are indexed to rhombohedral structures. TG/DSC technique evidenced a temperature of 330 °C needed for the precursor as the start point and 800 °C completion for perovskite phase formation. Slight distortion in XRD diffraction peaks was observed on substituting manganese with cobalt in B-site, and new peaks emerged. An attempt has been made to understand the effect of the B-site substitution of Co3+ ions in the lattice of LaMnO3 and their influence on catalytic total propylene oxidation efficiency. These compounds show a considerable increase in the activity of propylene oxidation to carbon dioxide and water and could be explored for hydrocarbon pollution control.